2003
DOI: 10.1063/1.1577120
|View full text |Cite
|
Sign up to set email alerts
|

Scaling in three-dimensional and quasi-two-dimensional rotating turbulent flows

Abstract: We have made velocity time series measurements (using hot film probes) and velocity field measurements (using particle image velocimetry) on turbulent flow in a rotating annulus. For low annulus rotation rates the Rossby number was of order unity and the flow was three-dimensional (3D), but at high rotation rates the Rossby number was only about 0.1, comparable to the value for oceans and the atmosphere on large length scales. The low Rossby number (quasi-geostrophic) flow was nearly two-dimensional (2D), as e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
101
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(114 citation statements)
references
References 25 publications
12
101
1
Order By: Relevance
“…The hot-wire measurements of Baroud et al 1 in a turbulent flow generated by radial jets in a rotating tank showed a transition from an intermittent to a nonintermittent behavior, characterized by a E(k) ∼ k −2 energy spectrum (i.e. ζ 2 = 1) and linear higher-order exponents ζ q = q/2.…”
Section: 8mentioning
confidence: 99%
“…The hot-wire measurements of Baroud et al 1 in a turbulent flow generated by radial jets in a rotating tank showed a transition from an intermittent to a nonintermittent behavior, characterized by a E(k) ∼ k −2 energy spectrum (i.e. ζ 2 = 1) and linear higher-order exponents ζ q = q/2.…”
Section: 8mentioning
confidence: 99%
“…Early Lagrangian measurements in grid-generated decaying rotating turbulence were performed using Particle Tracking by Dalziel (1992). Recently, Baroud et al (2003) investigated turbulent water jets in a rotating annulus at Re λ = 360, and found the turbulent flow to be highly intermittent, independently of the Rossby number. Morize, Moisy, and Rabaud recently performed several experiments of decaying rotating turbulence in large and small facilities (Morize et al, 2005, Morize and Moisy, 2006, Moisy et al, 2010, and described in details some aspects of the coupling between the inertial wave pattern and the decaying turbulent field using high-resolution PIV.…”
Section: Chapter 4 Large-scale Eulerian Flow Features In Rotating Turmentioning
confidence: 99%
“…Numerical simulations have shown that the faster growth of certain integral length scales is also related to the inhibited energy cascade. [21][22][23] Among the most recent experimental studies are those by Baroud et al, 13,14 Morize and co-workers, 15,24 and by Davidson an co-workers. 16, 17 Baroud and co-workers studied the flow in a rotating annulus with forcing created by pumping water into ͑out of͒ the annulus through an inner ͑outer͒ ring of holes on the bottom of the annulus.…”
Section: Introductionmentioning
confidence: 99%